Society of Cardiovascular Anesthesiologists Clinical Practice Update for Management of Acute Kidney Injury Associated With Cardiac Surgery. (12th May 2022) - Peng, Ke; McIlroy, David R.; Bollen, Bruce A.; Billings, Frederic T.; Zarbock, Alexander; Popescu, Wanda M.; Fox, Amanda A.; Shore-Lesserson, Linda; Zhou, Shaofeng; Geube, Mariya A.; Ji, Fuhai; Bhatia, Meena; et al.
Abstract : Cardiac surgery-associated acute kidney injury (CS-AKI) is common and is associated with increased risk for postoperative morbidity and mortality. Our recent survey of the Society of Cardiovascular Anesthesiologists (SCA) membership showed 6 potentially renoprotective strategies for which clinicians would most value an evidence-based review (ie, intraoperative target blood pressure, choice of specific vasopressor agent, erythrocyte transfusion threshold, use of alpha-2 agonists, goal-directed oxygen delivery on cardiopulmonary bypass [CPB], and the "Kidney Disease Improving Global Outcomes [KDIGO] bundle of care"). Thus, the SCA's Continuing Practice Improvement Acute Kidney Injury Working Group aimed to provide a practice update for each of these strategies in cardiac surgical patients based on the evidence from randomized controlled trials (RCTs). PubMed, EMBASE, and Cochrane library databases were comprehensively searched for eligible studies from inception through February 2021, with search results updated in August 2021. A total of 15 RCTs investigating the effects of the above-mentioned strategies on CS-AKI were included for meta-analysis. For each strategy, the level of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) methodology. Across the 6 potentially renoprotective strategies evaluated, current evidence for their use was rated as "moderate, " "low, " or "very low." Based on eligible RCTs, our analysis suggested using goal-directed oxygen delivery on CPB and the "KDIGO bundle of care" in high-risk patients to prevent CS-AKI (moderate level of GRADE evidence). Our results suggested considering the use of vasopressin in vasoplegic shock patients to reduce CS-AKI (low level of GRADE evidence). The decision to use a restrictive versus liberal strategy for perioperative red cell transfusion should not be based on concerns for renal protection (a moderate level of GRADE evidence). In addition, targeting a higher mean arterial pressure during CPB, perioperative use of dopamine, and use of dexmedetomidine did not reduce CS-AKI (a low or very low level of GRADE evidence). This review will help clinicians provide evidence-based care, targeting improved renal outcomes in adult patients undergoing cardiac surgery.